Flowing Through Time : History of the Lower Chattahoochee River. - Willoughby, Lynn, 1951- (Chattahoochee Valley legacy series, 2012)
This handsome, illustrated book chronicles the history of the Lower Chattahoochee River and the people who lived along its banks from prehistoric Indian settlement to the present day. In highly accessible, energetic prose, Lynn Willoughby takes readers down the Lower Chattahoochee River and through the centuries. On this journey, the author begins by examining the first encounters between Native Americans and European explorers and the international contest for control of the region in the 17th and 19th centuries. Throughout the book pays particular attention to the Chattahoochee's crucial r.